1994
DOI: 10.1007/bf02518915
|View full text |Cite
|
Sign up to set email alerts
|

Athermal physiological effects of microwaves on a cynobacterium Nostoc muscorum: evidence for EM-memory bits in water

Abstract: Athermal physiological effects of continuous wave and modulated microwaves were studied on a cynobacterium Nostoc muscorum. The study shows that different microwave frequencies in continuous wave and modulated modes produced significantly different physiological effects on the algae. Water-mediated bioeffects further present additional proof that water has the capability to remember the imposed electromagnetic field characteristics for an extended period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Another study with Wollea bharadwajae and C. licheniforme recorded that at field doses, N, P and K chemical fertilizers had varied responses from species to species, but 20 ppm NH 4 Cl inhibited N 2 -fixation (Singh, 1975 ). An alteration of heterocyst spacing in an intercalary heterocystous form, Nostoc muscorum by NH 4 salts, was reported (Singh et al , 1994 ) . This strain being programed for heterocyst differentiation and filament doubling concomitantly, the filament in urea influence was having greater length than those from N-depleted cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Another study with Wollea bharadwajae and C. licheniforme recorded that at field doses, N, P and K chemical fertilizers had varied responses from species to species, but 20 ppm NH 4 Cl inhibited N 2 -fixation (Singh, 1975 ). An alteration of heterocyst spacing in an intercalary heterocystous form, Nostoc muscorum by NH 4 salts, was reported (Singh et al , 1994 ) . This strain being programed for heterocyst differentiation and filament doubling concomitantly, the filament in urea influence was having greater length than those from N-depleted cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The reader may also refer to various commercial uses (see, for example, lgsonic.com/ultrasonic-algae-control/, Accessed date 7 July 2021). At relatively low frequencies and depending on the power density, microwave radiation affects the growth and metabolism of cyanobacteria [ 61 , 62 ]. Since the sensitivities of the vesicles differ between species, the ultrasonic frequency, radiation durations, and densities must be adopted accordingly.…”
Section: In-lake Treatmentsmentioning
confidence: 99%
“…However, a number of microbiological studies involving MW irradiation showed that the cell death was due to not only heat but also nonthermal (athermal) effects of the microwave electric field. Dreyfuss and Chipley (1980), Singh et al (1994), Banik et al (2002aBanik et al ( , 2002bBanik et al ( , 2003 tried to demonstrate the existence of nonthermal effects of microwave irradiation. They revealed that "microwaves athermally induced different biological effects by changing the structures by differentially partitioning the ions, altering the rate and/or direction of biochemical reactions" (Banik et al, 2003).…”
Section: Inactivation Mechanismmentioning
confidence: 99%